Time-use and environmental determinants of dropout from organized youth football and tennis - Ineke Deelen; Dick Ettema; Carlijn B. M. Kamphuis (BMC, 2018)
Abstract Background Many adolescents drop out of organized sports. Lack of motivation and competing priorities are known as important reasons for dropout. However, time use factors as well as environmental determinants have been largely neglected in the current literature on dropout from youth sports. The aim of this study is to investigate how (changes in) time use and characteristics of the physical environment determine dropout from football and tennis among adolescents. Methods Data on time use and background characteristics were collected through online surveys in 2015 and 2016 among adolescents aged 13-21 (N = 2555), including both the dropped outs and those who still continued membership of their football or tennis clubs. Physical environmental determinants (travel distance to the sports club, and neighbourhood density) were measured objectively. Binary logistic regression analyses were carried out for football and tennis separately to examine the associations between time use (time spent on various activities and changes related to the school and job situation), and environmental factors on the probability of dropping out from sports. Results Time spent on sports outside the context of the sports club, and time spent on social or voluntary activities at the sports club was positively associated with continuing being football and tennis members. Tennis players who changed schools or participated in two sports at the same time had a higher probability of dropping out, whereas tennis players who travelled greater distances from home to the tennis club were less likely to drop out. Conclusions Determinants of dropout differed between football and tennis. However, time use variables were important predictors of dropout from football as well as tennis, whereas environmental determinants hardly contributed to the prediction of dropout. To keep youths involved in organized sports, this study recommends that sports professionals should: 1) offer flexibility in training and competition schedules, 2) stimulate participation in social activities and voluntary work at the sports club, 3) pay special attention to their needs and preferences, and 4) encourage possibilities to practice and play sports outside of regular training hours, for instance at the sports club or at playgrounds or parks in the neighbourhood.